2017
DOI: 10.1001/jama.2017.11469
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Genotype-Guided Warfarin Dosing on Clinical Events and Anticoagulation Control Among Patients Undergoing Hip or Knee Arthroplasty

Abstract: IMPORTANCE Warfarin use accounts for more medication-related emergency department visits among older patients than any other drug. Whether genotype-guided warfarin dosing can prevent these adverse events is unknown.OBJECTIVE To determine whether genotype-guided dosing improves the safety of warfarin initiation. DESIGN, SETTING, AND PATIENTSThe randomized clinical Genetic Informatics Trial (GIFT) of Warfarin to Prevent Deep Vein Thrombosis included patients aged 65 years or older initiating warfarin for electiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
104
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(108 citation statements)
references
References 40 publications
4
104
0
Order By: Relevance
“…Subsequently, GBWD had less of an effect on anticoagulation control, and multiple-dose titrations might have had a greater role. The finding that the TTR was shorter in the GBWD group is similar to that observed in the GIFT, EU-PACT, and COUMAGEN-II trials Wen et al, 2017) but different from that in the COAG study and other Asian-based studies Gage et al, 2017;Syn et al, 2018;Zhe et al, 2018). Our study revealed that GBWD resulted in a lower prevalence of bleeding events related to anticoagulation therapy, which may have been due to superior primary outcomes.…”
Section: Discussionsupporting
confidence: 70%
“…Subsequently, GBWD had less of an effect on anticoagulation control, and multiple-dose titrations might have had a greater role. The finding that the TTR was shorter in the GBWD group is similar to that observed in the GIFT, EU-PACT, and COUMAGEN-II trials Wen et al, 2017) but different from that in the COAG study and other Asian-based studies Gage et al, 2017;Syn et al, 2018;Zhe et al, 2018). Our study revealed that GBWD resulted in a lower prevalence of bleeding events related to anticoagulation therapy, which may have been due to superior primary outcomes.…”
Section: Discussionsupporting
confidence: 70%
“…Using one of several existing NGS panels, including PGRNseq [7], AmpliSeq Pharmacogenomics Research Panel (thermofisher.com), or VeraCode ADME Core Panel (illumina.com), these variants indeed would be interrogated, but at the cost of requiring an additional test. Considering that every individual on average harbors six pharmacogenetically actionable variants, we identified several patients, who require significant PGx-based dosage adjustments, which has been shown to optimize treatment outcome for instance for the anticoagulants phenprocoumon or warfarin [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the case of SLE, the traditionally employed drug for treating fulminant lupus nephritis-cyclophosphamide-has lower effectiveness for remission in black and Hispanic patients compared to whites and Asians [8••]. Moreover, there has been a recent rise in RCTs involving genotype-guided dosing, where genetic factors are taken into consideration when prescribing appropriate medication dosing [31]. While these genotype-guided dosing RCTs could inform future tailored interventions, a major concern is that the under-representation of racial minorities could lead to ineffective treatment, or even be detrimental to the disease course in these groups.…”
Section: Discussionmentioning
confidence: 99%